Advances in chronic cerebral circulation insufficiency. (15th November 2017) - Zhou, Da; Meng, Ran; Li, Si‐Jie; Ya, Jing‐Yuan; Ding, Jia‐Yue; Shang, Shu‐Ling; Ding, Yu‐Chuan; Ji, Xun‐Ming
Summary: Chronic cerebral circulation insufficiency (CCCI) may not be an independent disease; rather, it is a pervasive state of long‐term cerebral blood flow insufficiency caused by a variety of etiologies, and considered to be associated with either occurrence or recurrence of ischemic stroke, vascular cognitive impairment, and development of vascular dementia, resulting in disability and mortality worldwide. This review summarizes the features and recent progress of CCCI, mainly focusing on epidemiology, experimental research, pathophysiology, etiology, clinical manifestations, imaging presentation, diagnosis, and potential therapeutic regimens. Some research directions are briefly discussed as well.